Composition for preparing solid-state polymer electrolyte and use thereof

CN116581377BActive Publication Date: 2026-10-27TSINGHUA UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310457928.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-25
Publication Date
2026-10-27
Estimated Expiration
2043-04-25

AI Technical Summary

Technical Problem

但是传统的二次电池也面临着有机液态电解质易挥发、泄露、燃烧甚至爆炸的风险

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116581377B_ABST
    Figure CN116581377B_ABST
Patent Text Reader

Abstract

The application provides a composition for preparing a solid-state polymer electrolyte and application thereof, the composition comprising the following components: an organic cyclic ether active diluent; a fluorinated oxygen-containing phosphate compound comprising a fluorinated alkyl phosphate, a fluorinated alkyl phosphite or a combination thereof; and an electrolyte salt, wherein the concentration of the fluorinated oxygen-containing phosphate compound in the composition is 5mmol / L-2000mmol / L. According to the application, the organic cyclic ether active diluent in the composition can undergo ring-opening polymerization under the initiation of the fluorinated oxygen-containing phosphate compound to obtain a solid-state polymer electrolyte, and the fluorinated oxygen-containing phosphate compound can also construct a tough inorganic component-rich solid-state electrolyte film at the positive and negative electrode interface in electrochemical cycling, the solid-state electrolyte film has excellent ion transport characteristics and a low ion diffusion energy barrier, so that the composition can obtain a solid-state polymer electrolyte with good and stable ion transport performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, and more specifically to a composition for preparing a solid polymer electrolyte and its application. Background Technology

[0002] Lithium-ion batteries, as a representative of rechargeable batteries, are widely used in digital electronic products, energy storage, drones, power tools, electric vehicles, and other products due to their high energy density, long cycle life, high safety, and fast charging capabilities. However, traditional rechargeable batteries also face the risks of volatile organic liquid electrolytes, leakage, combustion, and even explosion. Solid-state electrolytes, with their advantages of wide operating temperature range, long cycle life, and high energy density, have promising application prospects. However, current solid-state electrolytes suffer from poor ion transport performance, leading to large electrochemical polarization, making normal charging and discharging difficult, reducing the coulombic efficiency and cycle life of rechargeable batteries, and hindering the application of solid-state electrolytes.

[0003] Therefore, it is necessary to improve the ion transport performance of solid electrolytes. Summary of the Invention

[0004] This application provides a composition for preparing a solid polymer electrolyte and its application, which aims to form a solid polymer electrolyte with good ion transport properties.

[0005] In a first aspect, this application provides a composition for preparing a solid polymer electrolyte, comprising the following components: an organic cyclic ether active diluent; a fluorinated oxyphosphate compound, including fluoroalkyl phosphate, fluoroalkyl phosphite, or combinations thereof; and an electrolyte salt.

[0006] The concentration of the fluorinated oxyphosphate compound in the composition is 5 mmol / L to 2000 mmol / L.

[0007] According to this application, the organic cyclic ether active diluent in the composition can undergo ring-opening polymerization initiated by fluorinated oxyphosphate compounds to obtain a solid polymer electrolyte. This solid polymer electrolyte can achieve effective contact with the electrode active material and interface, thereby improving the ion transport performance of the solid polymer electrolyte. In addition, the fluorinated oxyphosphate compounds can also construct a tough, inorganic-rich solid electrolyte membrane at the positive and negative electrode interfaces during electrochemical cycling. This solid electrolyte membrane has excellent ion transport characteristics and a low ion diffusion barrier, thereby further improving the ion transport performance of the solid polymer electrolyte. Furthermore, it can reduce the polarization potential on the negative electrode side, suppress dendrite formation, and effectively block the oxidation of the ether chain segments on the positive electrode side under high voltage conditions, improving the stability of the solid polymer electrolyte and ensuring that the solid polymer electrolyte has stable ion transport performance.

[0008] In some embodiments of this application, the organic cyclic ether reactive diluent includes 1,3-dioxolane, 4-methyl-1,3-dioxolane, tert-butyl ethylene oxide-2-carboxylate, methyl (3-(ethylene oxide-2-yl)propyl)carbamate, (2-(ethylene oxide-2-yl)ethyl)carbamate, trimethoxy(8-(ethylene oxide-2-ylmethoxy)octyl)silane, 1,3,5-triglycidyl-S-triazinetrione, 2-((1-ethyl) At least one of the following: (2,3-epoxypropoxy)methyl)ethylene oxide, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 3-(perfluorobutane)-1,2-epoxypropane, 3-(perfluorohexane)-1,2-epoxypropane, 4-[(2,3-epoxypropoxy)methyl]-2,2-dimethyl-1,3-dioxolane, 1,4-bis(epoxyethylene-2-ylmethoxy)butane, and 2,2'-[oxybis(2,1-ethyleneoxymethylene)]bisethylene oxide.

[0009] In some embodiments of this application, the fluorinated oxyphosphate compounds include at least one of tris(2,2,2-trifluoroethyl) phosphate, tris(2,2-difluoroethyl) phosphate, tris(2,2,3,3-tetrafluoropropyl) phosphate, tris(1H,1H,5H-octafluoro-n-pentyl) phosphate, bis(2,2,2-trifluoroethyl) phosphite, tris(1,1,1,3,3,3-hexafluoro-2-propyl) phosphate, tris(1,1,1,3,3,3-hexafluoro-2-propyl) phosphite, 1,1-difluoro-2-methylpropyl-2-yl diethyl phosphate, and 2-(2,2,2-trifluoroethoxy)-1,3,2-dioxaphosphacyclopentane 2-oxide.

[0010] Optionally, the fluorinated oxyphosphate compound includes tris(2,2,2-trifluoroethyl) phosphate.

[0011] In some embodiments of this application, the electrolyte salt may be selected from lithium salt, sodium salt, potassium salt, rubidium salt, calcium salt, magnesium salt, zinc salt, aluminum salt, and tin salt, and the concentration of the electrolyte salt in the composition is 0.1 mol / L to 5 mol / L.

[0012] In some embodiments of this application, the composition further includes a plasticizer, wherein the plasticizer comprises 1% to 70% by volume in the composition;

[0013] Optionally, the plasticizer includes at least one of dimethyl carbonate, diethyl carbonate, ethylene carbonate, methyl propyl carbonate, propylene carbonate, methyl ethyl carbonate, butenyl carbonate, γ-butyrolactone, isopropyl methyl carbonate, tetrahydrofuran, 1,4-butyrolactone, butenyl carbonate, dimethyltetrahydrofuran, 1,2-dimethoxyethane, methyl butyl carbonate, dibutyl carbonate, methyl ester, methyl acetate, dipropyl carbonate, methyl propionate, methyl formate, N-ethylpyrrolidone, N-methyl-2-pyrrolidone, triethyl phosphate, trimethyl phosphate, tripropyl phosphate, dimethyl sulfoxide, succinic acid, fluoroethylene carbonate, vinylene carbonate, and propylene sulfite.

[0014] In some embodiments of this application, the composition further includes a film-forming additive, wherein the film-forming additive is present in the composition at a mass percentage of 0.2% to 20%.

[0015] Optionally, the film-forming additive includes at least one of fluoroethylene carbonate, vinylene carbonate, and propylene sulfite.

[0016] Secondly, this application provides a secondary battery, comprising: a positive electrode, a negative electrode, and...

[0017] Solid polymer electrolyte formed from the composition according to any embodiment of the first aspect.

[0018] In some embodiments of this application, the secondary battery is any one of lithium metal battery, potassium metal battery, rubidium metal battery, calcium metal battery, magnesium metal battery, zinc metal battery, aluminum metal battery, and tin metal battery.

[0019] Thirdly, this application provides a method for preparing a secondary battery, comprising the following steps:

[0020] A composition according to any embodiment of the first aspect is added between the positive electrode and the negative electrode, and the composition is solidified between the positive electrode and the negative electrode to form a solid polymer electrolyte, thereby obtaining a secondary battery.

[0021] In some embodiments of this application, the curing conditions are specifically: standing at 20℃ to 80℃ for more than 30 seconds.

[0022] Fourthly, this application provides an electrical device, comprising: a secondary battery according to any embodiment of the second aspect or a secondary battery prepared by the preparation method according to any embodiment of the third aspect. Attached Figure Description

[0023] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.

[0024] Figure 1 This is a structural model diagram of the solid electrolyte membrane rich in inorganic components on the positive and negative electrode surfaces after cycling of a solid lithium metal battery using the solid polymer electrolyte of this application.

[0025] Figure 2 This is a graph showing the properties of the composition used in Example 1 for preparing the solid polymer electrolyte after being allowed to stand at room temperature for 12 hours to polymerize.

[0026] Figure 3 The graph shows the LSV test results of the lithium stainless steel coin cells obtained in Example 1 and Comparative Examples 1 and 2.

[0027] Figure 4 These are rate performance graphs of symmetrical cells with solid polymer electrolytes in Examples 2 and 4 under different current density rates.

[0028] Figure 5 The graphs show the rate performance of symmetrical cells with solid polymer electrolytes in Examples 3 and 4 under different current density rates.

[0029] Figure 6 This is a rate performance graph of the Li||LFP full cell with solid polymer electrolyte in Example 5 under current density conditions of 0.1C, 0.2C, 0.5C, and 1.0C.

[0030] Figure 7 This is a rate performance graph of the Li||NCM full cell with solid polymer electrolyte in Example 6 under current density conditions of 0.05C, 0.1C, 0.2C, and 0.5C.

[0031] The accompanying drawings illustrate specific embodiments of this application, which will be described in more detail below. These drawings and descriptions are not intended to limit the scope of the concept in any way, but rather to illustrate the concept of this application to those skilled in the art through reference to particular embodiments. Detailed Implementation

[0032] The various embodiments or implementation schemes in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments.

[0033] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with an embodiment or example is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0034] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified.

[0035] As mentioned in the background section above, solid-state electrolytes have significant advantages over organic liquid electrolytes and are one of the important development directions in the battery field.

[0036] Currently, solid electrolytes are generally divided into inorganic solid electrolytes and solid polymer electrolytes. The former, often based on oxides and sulfides, possesses advantages such as high ionic conductivity and a wide electrochemical window, but faces challenges such as cumbersome processing, high brittleness, and high solid-solid interface impedance in battery assembly. Therefore, using solid polymer electrolytes, which offer good flexibility and processability, is a feasible strategy to address this problem. Solid polymer electrolytes prepared by conventional in-situ polymerization methods struggle to achieve sufficient contact between the electrolyte and electrode materials, resulting in large electrochemical polarization and difficulty in normal charge-discharge operation. This phenomenon is particularly pronounced when matched with cathode materials that have high active surface loading.

[0037] Furthermore, to address the challenge of achieving sufficient contact between the electrolyte and electrode materials in solid polymer electrolytes, in-situ polymerization can be employed. This involves using a softer ether-based segment gel polymer electrolyte as the electrolyte matrix, achieving effective contact between electrode material particles and interfaces through in-situ polymerization within the battery. While this significantly reduces electrochemical polarization to some extent, it fails to address the issues of easy oxidation of ether-based segments, poor high-voltage tolerance, and rampant dendrite growth during cycling. Therefore, it is often necessary to introduce other functional additives to construct stable positive and negative electrode interfaces. Some researchers have even employed complex and cumbersome preparation processes, such as vapor deposition, atomic deposition, and molecular deposition, to pre-construct stable positive and negative electrode interfaces to improve the electrolyte's voltage resistance. However, the large number of electrolyte components and the use of sophisticated equipment hinder commercial cost-effectiveness.

[0038] Based on the above problems, this application starts from the preparation of in-situ gel polymer electrolytes and provides a composition for preparing solid polymer electrolytes and its application. The solid polymer electrolyte obtained by this composition can effectively improve the above technical problems. The technical solution provided by this application will be described in detail below.

[0039] In a first aspect, this application provides a composition for preparing a solid polymer electrolyte, comprising the following components: an organic cyclic ether active diluent; a fluorinated oxyphosphate compound, including fluoroalkyl phosphate, fluoroalkyl phosphite, or combinations thereof; and an electrolyte salt.

[0040] The concentration of fluorinated oxyphosphate compounds in the composition is 5 mmol / L to 2000 mmol / L.

[0041] According to this application, in the above composition, the organic cyclic ether active diluent can undergo ring-opening polymerization under the initiation of fluorinated oxyphosphate compounds to obtain a solid polymer electrolyte. The conditions of this ring-opening polymerization reaction are relatively mild. Therefore, during the battery preparation process, the composition can be added between the positive and negative electrodes to form a solid polymer electrolyte through in-situ polymerization. Since the solid polymer electrolyte is a relatively soft ether-based segmental gel polymer, it can achieve effective contact with the electrode active material and interface, thereby improving the ion transport performance of the solid polymer electrolyte and significantly reducing electrochemical polarization during battery charging and discharging.

[0042] In addition, when using fluorinated oxyphosphate compounds as initiators for the ring-opening polymerization of organic cyclic ether active diluents, the inventors discovered that fluorinated oxyphosphate compounds can also participate in the formation of positive and negative electrode solid electrolyte films during the electrochemical cycling process of the battery. Moreover, the formed positive and negative electrode solid electrolyte films are rich in inorganic components. Compared with general solid electrolyte films which are rich in organic components, they have higher strength and toughness, and have excellent ion transport characteristics and lower ion diffusion energy barriers.

[0043] Based on this, the use of this solid polymer electrolyte allows for the formation of a robust positive electrode solid electrolyte membrane (CEI membrane) at the positive electrode interface. This membrane is not easily damaged during battery cycling and exhibits excellent stability. This effectively prevents the oxidation of ether segments in the solid polymer electrolyte under high voltage (greater than or equal to 4.3V), thereby improving the stability of the solid polymer electrolyte, ensuring stable contact between the solid polymer electrolyte and the positive electrode interface, and enhancing the ion transport performance of the solid polymer electrolyte. Furthermore, the negative electrode solid electrolyte membrane (SEI membrane) formed at the negative electrode interface possesses excellent ion transport characteristics and a low ion diffusion barrier. Therefore, the negative electrode interface has a smaller polarization potential, which facilitates uniform ion deposition and suppresses dendrite formation, thereby improving the coulombic efficiency and cycle life of the secondary battery.

[0044] It is understood that the composition includes electrolyte salts, which primarily provide conductive ions and participate in the formation of solid electrolytes at both the positive and negative electrodes. This application does not limit the type of electrolyte salt in the composition; those skilled in the art can select it according to actual needs.

[0045] According to this application, the concentration of the fluorinated oxyphosphate compound in the composition is 5 mmol / L to 2000 mmol / L. Based on the above description of the fluorinated oxyphosphate compound in the composition, it can simultaneously act as an initiator and a film-forming additive. If the concentration of the fluorinated oxyphosphate compound is too low, on the one hand, the polymerization reaction rate may be slow, making it difficult to obtain a solid polymer electrolyte; on the other hand, it may not be possible to form a solid electrolyte membrane rich in inorganic components, affecting the strength and toughness of the solid electrolyte and resulting in poor ion transport performance. If the concentration of the fluorinated oxyphosphate compound is too high, on the one hand, the polymerization reaction rate will be too fast, making it impossible to form a stable solid polymer electrolyte; on the other hand, excessive concentration may affect the viscosity of the composition, making it difficult to process and utilize. Furthermore, an excessively thick solid electrolyte membrane may also affect ion conduction. Therefore, the concentration of the fluorinated oxyphosphate compound in the composition should be controlled within the range of 5 mmol / L to 2000 mmol / L, thus obtaining a solid polymer electrolyte with good ion transport performance and the ability to form tough positive and negative electrode solid electrolyte membranes.

[0046] Therefore, it can be understood that the fluorinated oxyphosphate compounds in the composition provided in this application can simultaneously act as initiators and film-forming additives, thus avoiding the adverse effects that initiators in solid polymer electrolytes may have on ion transport. At the same time, since the content of solutes other than electrolyte salts can be reduced, the content of electrolyte salts can be appropriately increased to increase the number of ions that can be conducted in the solid polymer electrolyte and improve the ion transport performance of the solid polymer electrolyte.

[0047] In addition, the composition provided in this application has simple components and can be prepared simply by mixing the components evenly. Therefore, it is cost-effective for commercial applications and suitable for large-scale production applications.

[0048] In some embodiments of this application, the organic cyclic ether reactive diluents include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tert-butyl ethylene oxide-2-carboxylate, methyl (3-(ethylene oxide-2-yl)propyl)carbamate, (2-(ethylene oxide-2-yl)ethyl)carbamate, trimethoxy(8-(ethylene oxide-2-ylmethoxy)octyl)silane, 1,3,5-triglycidyl-S-triazinetrione, 2-((1-ethoxy) At least one of the following: (2,3-epoxypropoxy)methyl)ethylene oxide, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 3-(perfluorobutane)-1,2-epoxypropane, 3-(perfluorohexane)-1,2-epoxypropane, 4-[(2,3-epoxypropoxy)methyl]-2,2-dimethyl-1,3-dioxolane, 1,4-bis(epoxyethylene-2-ylmethoxy)butane, and 2,2'-[oxybis(2,1-ethyleneoxymethylene)]bisepoxyethylene.

[0049] In the above embodiments, some commonly used organic cyclic ether reactive diluents in the art are specifically listed, and those skilled in the art can select them as needed. All of the above-mentioned organic cyclic ether reactive diluents can, under the initiation of an initiator, yield stable solid polymer electrolytes with good contact with the positive and negative electrode interfaces, exhibiting excellent ion transport performance. It should be noted that organic cyclic ether reactive diluents are not limited to the above-mentioned types; those skilled in the art can select any organic cyclic ether reactive diluent from the prior art as needed.

[0050] In some embodiments of this application, the fluorinated oxyphosphate compounds include at least one of tris(2,2,2-trifluoroethyl) phosphate, tris(2,2-difluoroethyl) phosphate, tris(2,2,3,3-tetrafluoropropyl) phosphate, tris(1H,1H,5H-octafluoro-n-pentyl) phosphate, bis(2,2,2-trifluoroethyl) phosphite, tris(1,1,1,3,3,3-hexafluoro-2-propyl) phosphate, tris(1,1,1,3,3,3-hexafluoro-2-propyl) phosphite, 1,1-difluoro-2-methylpropyl-2-yl diethyl phosphate, and 2-(2,2,2-trifluoroethoxy)-1,3,2-dioxaphosphacyclopentane 2-oxide.

[0051] Optionally, fluorinated oxyphosphate compounds include tris(2,2,2-trifluoroethyl) phosphates.

[0052] In the above embodiments, several fluorinated oxyphosphate compounds that can be used as initiators and film-forming additives are specifically listed, and those skilled in the art can select them as needed. Using the above-mentioned types of fluorinated oxyphosphate compounds, ring-opening polymerization of organic cyclic ether reactive diluents can be initiated under relatively mild conditions, and a solid electrolyte membrane rich in inorganic components can also be formed during electrochemical cycling. It should be noted that fluorinated oxyphosphate compounds are not limited to the above-mentioned types, and those skilled in the art can select any fluorinated oxyphosphate compound from the prior art as needed.

[0053] Furthermore, when the fluorinated oxyphosphate compounds include tris(2,2,2-trifluoroethyl) phosphate, the resulting solid polymer electrolyte exhibits better ion transport performance. The solid electrolyte membrane formed can effectively suppress dendrite formation and effectively prevent the oxidation of ether segments under high voltage conditions, thereby enabling the battery to have higher coulombic efficiency and cycle life.

[0054] In some embodiments of this application, the electrolyte salt may be selected from lithium salt, sodium salt, potassium salt, rubidium salt, calcium salt, magnesium salt, zinc salt, aluminum salt, and tin salt, and the concentration of the electrolyte salt in the composition is 0.1 mol / L to 5 mol / L.

[0055] In some of the above embodiments, the electrolyte salt can be selected from one of lithium salt, sodium salt, potassium salt, rubidium salt, calcium salt, magnesium salt, zinc salt, aluminum salt, and tin salt. It is understood that the corresponding electrolyte salt is selected according to the type of battery. As an example, in a lithium battery, lithium salt is selected as the electrolyte salt. The specific type of lithium salt can be selected according to actual needs. For example, lithium salt can include at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium nitrate, lithium trifluoromethanesulfonate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium dioxalate borate, lithium perchlorate, and lithium difluorooxalate borate.

[0056] Meanwhile, the concentration of the electrolyte salt in the composition is further limited. It is understood that the higher the concentration of the electrolyte salt, the more ions that can be used for conduction in the resulting solid polymer electrolyte, and the better the ion transport performance. However, if the electrolyte concentration is too high, it will lead to excessive viscosity of the composition, which will affect the polymerization of organic cyclic ethers and the contact between the solid polymer electrolyte and the positive and negative electrode materials. This will hinder ion conduction and result in poor ion transport performance of the resulting solid polymer electrolyte. Therefore, the concentration of the electrolyte salt in the composition can be 0.1 mol / L to 5 mol / L.

[0057] In some embodiments of this application, the composition further includes a plasticizer, wherein the volume fraction of the plasticizer in the composition is 1% to 70%;

[0058] Optionally, the plasticizer includes at least one of dimethyl carbonate, diethyl carbonate, ethylene carbonate, methyl propyl carbonate, propylene carbonate, methyl ethyl carbonate, butenyl carbonate, γ-butyrolactone, isopropyl methyl carbonate, tetrahydrofuran, 1,4-butyrolactone, butenyl carbonate, dimethyltetrahydrofuran, 1,2-dimethoxyethane, methyl butyl carbonate, dibutyl carbonate, methyl ester, methyl acetate, dipropyl carbonate, methyl propionate, methyl formate, N-ethylpyrrolidone, N-methyl-2-pyrrolidone, triethyl phosphate, trimethyl phosphate, tripropyl phosphate, dimethyl sulfoxide, succinic acid, fluoroethylene carbonate, vinylene carbonate, and propylene sulfite.

[0059] In some of the above embodiments, a plasticizer may also be added to the composition. Its function is to further improve the contact stability between the solid polymer electrolyte and the positive and negative electrode sheets, and to promote the dispersion of electrolyte salts in the composition. At the same time, it can increase the dielectric constant of the solid polymer electrolyte and appropriately reduce the degree of solidification of the solid polymer electrolyte, which is more conducive to ion conduction, thereby further improving the ion transport performance of the solid polymer electrolyte.

[0060] Meanwhile, the volume fraction of the plasticizer in the composition is further limited. It is understood that if the volume fraction is too low, the performance improvement of the solid polymer electrolyte will be limited. If the volume fraction is too high, the viscosity of the composition will increase, affecting the ring-opening polymerization reaction of the organic cyclic ether reactive diluent, which is not conducive to the formation of a stable solid polymer electrolyte. Therefore, the volume fraction of the plasticizer in the composition can be 1% to 70%.

[0061] Furthermore, several plasticizers are specifically listed in the above embodiments, and those skilled in the art can select at least one of them according to actual needs. These plasticizers are generally commonly used organic electrolyte solvents in the art; appropriate addition can increase the dielectric constant of the solid polymer electrolyte, which is beneficial for improving the ion conduction rate in the solid polymer electrolyte. It is understood that plasticizers are not limited to the above-mentioned types, and those skilled in the art can select existing compounds that can be used as plasticizers according to actual needs.

[0062] In some embodiments of this application, the composition further includes a film-forming additive, wherein the film-forming additive is present in the composition at a mass percentage of 0.2% to 20%.

[0063] Optionally, the film-forming additive includes at least one of fluoroethylene carbonate, vinylene carbonate, and propylene sulfite.

[0064] In some of the above embodiments, the composition may further include film-forming additives, which can also participate in the formation of the positive and negative electrode solid electrolyte membranes. These additives can work with the fluorinated oxyphosphate compounds in the composition to form a more robust solid electrolyte membrane, further improving the ion transport performance of the solid polymer electrolyte, thereby reducing polarization, suppressing dendrite formation, and preventing the oxidation of ether segments in the electrolyte, thereby improving the coulombic efficiency and cycle life of the battery.

[0065] The composition also specifies the mass percentage of film-forming additives. If the content of film-forming additives is too low, there will not be enough additives to participate in the formation of the solid electrolyte membrane, thus making it difficult for them to play their role. If there are too many film-forming additives, on the one hand, it will affect the ring-opening polymerization of organic cyclic ether reactive diluents, affecting the stability of the solid polymer electrolyte; on the other hand, too much additives will affect the conduction of ions in the solid polymer electrolyte. Therefore, the mass percentage of film-forming additives in the composition can be 0.2% to 20%.

[0066] Furthermore, the above embodiments also list several commonly used film-forming additives in the art, and those skilled in the art can select at least one of them according to actual needs. It is understood that film-forming additives are not limited to the above-mentioned types, and those skilled in the art can select any compound in the prior art that can be used as a film-forming additive as needed.

[0067] Secondly, this application provides a secondary battery, comprising: a positive electrode, a negative electrode, and...

[0068] Solid polymer electrolyte formed from the composition according to any embodiment of the first aspect.

[0069] According to this application, since the secondary battery comprises a solid polymer electrolyte formed from the composition of any embodiment of the first aspect, it has the beneficial effects of the first aspect.

[0070] In this application, there are no restrictions on the types of positive and negative electrode sheets. Those skilled in the art can choose any known positive and negative electrode sheets in the prior art as needed.

[0071] In some embodiments of this application, the secondary battery is any one of lithium metal battery, potassium metal battery, rubidium metal battery, calcium metal battery, magnesium metal battery, zinc metal battery, aluminum metal battery, and tin metal battery.

[0072] In some of the above embodiments, the secondary battery is any one of lithium metal battery, potassium metal battery, rubidium metal battery, calcium metal battery, magnesium metal battery, zinc metal battery, aluminum metal battery, and tin metal battery. It is understood that lithium metal battery, as represented by lithium metal battery, has a meaning known in the art, namely, a battery that uses lithium metal as the negative electrode. This is because the lithium negative electrode has an ultra-high theoretical specific capacity of 3860 mAh / g, a low electrode potential of -3.04V (vs. standard hydrogen electrode), and a capacitance of 0.534 g / cm³. 3 The lithium metal battery has advantages such as low density. However, lithium dendrite formation during charging and discharging significantly reduces the battery's lifespan and safety. In this application, the solid polymer electrolyte obtained using the composition of any embodiment of the first aspect allows the lithium metal battery to form inorganic-rich positive and negative electrode solid electrolyte films after cycling, as shown in the structural model diagram below. Figure 1 As described above, due to the excellent ion transport characteristics and low ion diffusion barrier of the SEI film, the negative electrode side has a small polarization potential, which facilitates smooth lithium deposition and effectively suppresses the formation of lithium dendrites. Furthermore, the SEI film has high strength and toughness, preventing lithium dendrites from penetrating the solid polymer electrolyte even if a small amount of lithium dendrites appear, thereby improving the safety performance of the lithium metal battery. Therefore, the secondary battery can be a lithium metal battery, effectively increasing its energy density.

[0073] Thirdly, this application provides a method for preparing a secondary battery, comprising the following steps:

[0074] A composition according to any embodiment of the first aspect is added between the positive electrode and the negative electrode, and the composition is cured between the positive electrode and the negative electrode to form a solid polymer electrolyte, thereby obtaining a secondary battery.

[0075] According to this application, since the preparation method uses a solid polymer electrolyte formed from the composition of any embodiment of the first aspect, it has the beneficial effects of the first aspect. Furthermore, the preparation method employs in-situ polymerization, thus allowing for closer direct contact between the solid polymer electrolyte and the electrode active material, thereby significantly reducing interfacial impedance and effectively mitigating the volume expansion problem of the secondary battery during cycling.

[0076] In addition, the preparation method is simple, and the composition can be directly added between the positive electrode and the negative electrode and cured, making it suitable for industrial production applications.

[0077] In some embodiments of this application, after the composition is cured between the positive and negative electrode sheets to form a solid polymer electrolyte, the process may further include steps such as winding, welding tabs, encapsulation, settling, formation, and shaping. No further limitations are made here, and each step can be performed using any method known in the prior art.

[0078] In some embodiments of this application, the curing conditions are specifically: standing at 20℃~80℃ for more than 30 seconds.

[0079] In some of the above embodiments, the curing conditions are further defined as standing at 20°C to 80°C for at least 30 seconds. Because the compositions provided in any embodiment of the first aspect of this application can rapidly form polymer gels under relatively mild conditions, initiated by fluorinated oxyphosphate compounds, yielding solid polymer electrolytes, this avoids complex preparation processes and sophisticated equipment, is simple and easy to implement, has lower costs, and is more suitable for industrial production.

[0080] Fourthly, this application provides an electrical device, comprising: a secondary battery prepared according to any embodiment of the second aspect or a secondary battery prepared according to any embodiment of the third aspect.

[0081] According to this application, since the electrical device includes a secondary battery according to any embodiment of the second aspect or a secondary battery prepared according to the preparation method of any embodiment of the third aspect, the electrical device has the beneficial effects of the second or third aspect.

[0082] The electrical equipment used in this application is not particularly limited and can be any electrical equipment known in the prior art. In some embodiments, the electrical equipment may include, but is not limited to, laptops, pen input computers, mobile computers, e-book players, portable telephones, portable fax machines, portable copiers, portable printers, stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini CDs, transceivers, electronic notebooks, calculators, memory cards, portable recorders, radios, backup power supplies, motors, automobiles, motorcycles, electric bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries, and lithium-ion capacitors, etc.

[0083] The following describes embodiments of this application. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.

[0084] Example 1

[0085] The specific steps for preparing the composition for the preparation of solid polymer electrolytes in an argon glove box (O2, H2O < 1 ppm) are as follows:

[0086] (1) Weigh 5.742 g of lithium bis(trifluoromethanesulfonylimide) and dissolve it in 10 mL of 1,3-dioxolane to obtain a conventional precursor electrolyte.

[0087] (2) Take an appropriate amount of the above conventional precursor electrolyte, weigh tris(2,2,2-trifluoroethyl) phosphate (weigh tris(2,2,2-trifluoroethyl) phosphate at a concentration of 0.36 mol / L) at a mass fraction of 8 wt%, add it to the conventional precursor electrolyte prepared above and mix evenly to obtain a composition for preparing solid polymer electrolyte.

[0088] (3) Take an appropriate amount of the above-mentioned composition for preparing solid polymer electrolytes into a sample tube, and after standing at room temperature for 12 hours, its gel polymerization properties are as follows. Figure 2 As shown in the results, it can be seen that fluorinated oxyphosphate compounds can indeed polymerize into a transparent gel state, which is consistent with the experimental design. Furthermore, 100 μL of the composition used to prepare the solid polymer electrolyte was added dropwise to a lithium-stainless steel coin cell. After standing at room temperature for 12 hours, the LSV was tested at a scan rate of 0.5 mV / s within the voltage range of 0–7 V. The results are as follows. Figure 3 As shown.

[0089] Comparative Example 1

[0090] The specific steps for preparing the composition for the preparation of solid polymer electrolytes in an argon glove box (O2, H2O < 1 ppm) are as follows:

[0091] (1) Weigh 5.742 g of lithium bis(trifluoromethanesulfonylimide) and dissolve it in 10 mL of 1,3-dioxolane to obtain a conventional precursor electrolyte, which is the composition used to prepare solid polymer electrolytes.

[0092] (2) 100 μL of the above-mentioned composition for preparing solid polymer electrolyte was added dropwise to a lithium-stainless steel coin cell. After standing at room temperature for 12 h, LSV was tested at a scan rate of 0.5 mV / s within the voltage range of 0–7 V. The results are as follows: Figure 3 As shown.

[0093] Comparative Example 2

[0094] The specific steps for preparing the composition for the preparation of solid polymer electrolytes in an argon glove box (O2, H2O < 1 ppm) are as follows:

[0095] (1) Weigh 5.742 g of lithium bis(trifluoromethanesulfonylimide) and dissolve it in 10 mL of 1,3-dioxolane to obtain a conventional precursor electrolyte.

[0096] (2) Take an appropriate amount of conventional precursor electrolyte and weigh aluminum trifluoromethanesulfonate (a conventional initiator) at a concentration of 0.36 mol / L. Add it to the conventional precursor electrolyte prepared above and mix evenly to obtain a composition for preparing solid polymer electrolyte.

[0097] (3) 100 μL of the composition used to prepare the solid polymer electrolyte was dropped into a lithium-stainless steel coin cell. After standing at room temperature for 12 h, the LSV was tested at a scan rate of 0.5 mV / s within the voltage range of 0–7 V. The results are as follows: Figure 3 As shown.

[0098] according to Figure 3 The results show that the withstand voltage of conventional 1,3-dioxolane in Comparative Example 1 is only 3.05V, indicating that it is easily decomposed under high voltage and cannot be matched with high-voltage positive electrode. The solid polymer electrolyte obtained by using conventional initiator in Comparative Example 2 has a withstand voltage of only 4.21V, which is also unstable under high voltage and cannot be applied to high-voltage positive electrode system. However, after adding fluorinated oxyphosphate compounds in Example 1, its withstand voltage can be increased to 4.65V, which has the potential to be matched with high-voltage positive electrode. The possible reason is that adding fluorinated oxyphosphate compounds can construct stable positive and negative electrode solid electrolyte films during charge and discharge.

[0099] Example 2:

[0100] The specific steps for preparing the solid polymer electrolyte composition in an argon glove box (O2, H2O < 1 ppm) are as follows:

[0101] (1) Weigh 5.742 g of lithium bis(trifluoromethanesulfonylimide) and 0.287 g of lithium difluorooxalate borate, and dissolve them in a mixed solvent of 9.5 mL of 1,3-dioxolane and 0.5 mL of triethyl phosphate to obtain a conventional precursor electrolyte.

[0102] (2) Take an appropriate amount of the above conventional precursor electrolyte, weigh tris(2,2,2-trifluoroethyl) phosphate at a concentration of 0.36 mol / L, add it to the above-prepared conventional precursor electrolyte and mix evenly to obtain a solid polymer electrolyte composition.

[0103] Example 3

[0104] The specific steps for preparing the solid polymer electrolyte composition in an argon glove box (O2, H2O < 1 ppm) are as follows:

[0105] (1) Weigh 5.742 g of lithium bis(trifluoromethanesulfonylimide) and 0.287 g of lithium difluorooxalate borate, and dissolve them in a mixed solvent of 5 mL of 1,3-dioxolane and 5 mL of fluoroethylene carbonate to obtain a conventional precursor electrolyte.

[0106] (2) Take an appropriate amount of the above conventional precursor electrolyte, weigh tris(2,2,2-trifluoroethyl) phosphate at a concentration of 0.36 mol / L, add it to the above-prepared conventional precursor electrolyte and mix evenly to obtain a solid polymer electrolyte composition.

[0107] Example 4:

[0108] The specific steps for preparing the solid polymer electrolyte composition in an argon glove box (O2, H2O < 1 ppm) are as follows:

[0109] (1) Weigh 5.742 g of lithium bis(trifluoromethanesulfonylimide) and 0.287 g of lithium difluorooxalateborate, dissolve them in 10 mL of 1,3-dioxolane to obtain a conventional precursor electrolyte.

[0110] (2) Take an appropriate amount of the above conventional precursor electrolyte, weigh tris(2,2,2-trifluoroethyl) phosphate at a concentration of 0.36 mol / L, add it to the above-prepared conventional precursor electrolyte and mix evenly to obtain a solid polymer electrolyte composition.

[0111] 100 μL of each of the solid polymer electrolyte compositions obtained in Examples 2-4 were dropped into a lithium-ion symmetric coin cell. After standing at room temperature for 12 h, rate performance tests were performed under different current density conditions for 1 h of deposition / stripping. The results are as follows: Figure 4 and Figure 5 As shown.

[0112] according to Figure 4 and Figure 5 The results show that the ion transport performance of fluorinated oxyphosphate compounds in Examples 2 and 3 is better than that in Example 4. This may be because the solid polymer electrolyte obtained by conventional 1,3-dioxolane in Comparative Example 4 has a high degree of solidification after polymerization, resulting in relatively low ion conductivity, thus leading to high polarization and easy short circuit. In contrast, the addition of an appropriate amount of plasticizer in Examples 2 and 3 can achieve more stable lithium deposition / stripping performance, indicating that the addition of an appropriate amount of plasticizer can increase ion conductivity and improve rate performance.

[0113] Example 5:

[0114] The specific steps for preparing the solid polymer electrolyte composition in an argon glove box (O2, H2O < 1 ppm) are as follows:

[0115] (1) Weigh 5.742 g of lithium bis(trifluoromethanesulfonylimide) and 0.287 g of lithium difluorooxalate borate, and dissolve them in a mixed solvent of 9.5 mL of 1,3-dioxolane and 0.5 mL of triethyl phosphate to obtain a conventional precursor electrolyte.

[0116] (2) Take an appropriate amount of the above-mentioned conventional precursor electrolyte, weigh tris(2,2,2-trifluoroethyl) phosphate at a concentration of 0.36 mol / L, add it to the conventional precursor electrolyte prepared above and mix evenly to obtain a composition of solid polymer electrolyte.

[0117] (3) 100 μL of the above-mentioned solid polymer electrolyte composition was added dropwise to a lithium iron phosphate cathode coin cell. After standing at room temperature for 12 h, the charge / discharge voltage range was controlled at 2.0-4.0 V. Rate performance tests were conducted under current density conditions of 0.1C, 0.2C, 0.5C, and 1.0C. The results are as follows: Figure 6 As shown.

[0118] Example 6:

[0119] The specific steps for preparing the solid polymer electrolyte composition in an argon glove box (O2, H2O < 1 ppm) are as follows:

[0120] (1) Weigh 5.742 g of lithium bis(trifluoromethanesulfonylimide) and 0.287 g of lithium difluorooxalate borate, and dissolve them in a mixed solvent of 5 mL of 1,3-dioxolane and 5 mL of fluoroethylene carbonate to obtain a conventional precursor electrolyte.

[0121] (2) Take an appropriate amount of the above-mentioned conventional precursor electrolyte, weigh tris(2,2,2-trifluoroethyl) phosphate at a concentration of 0.36 mol / L, add it to the conventional precursor electrolyte prepared above and mix evenly to obtain a composition of solid polymer electrolyte.

[0122] (3) 100 μL of the above-mentioned solid polymer electrolyte composition was added dropwise to a lithium-ion ternary cathode coin cell. After standing at room temperature for 12 h, the charge / discharge voltage range was controlled at 2.6-4.3 V. Rate performance tests were conducted under current density conditions of 0.05 C, 0.1 C, 0.2 C, and 0.5 C. The results are as follows: Figure 7 As shown.

[0123] according to Figure 6 and Figure 7 It is evident that Examples 5 and 6 exhibit good rate performance in different full-cell configurations, particularly in the high-voltage system of Example 6, where excellent rate performance is still maintained. This demonstrates that the solid polymer electrolyte provided in this application possesses good ionic conductivity and excellent stability at high voltages, significantly improving the rate performance of the battery.

[0124] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.

Claims

1. A composition for preparing a solid polymer electrolyte, characterized in that, Includes the following components: organic cyclic ether reactive diluent; Fluorinated oxyphosphate compounds, wherein the fluorinated oxyphosphate compounds include at least one selected from the following: tris(2,2,2-trifluoroethyl) phosphate, tris(2,2-difluoroethyl) phosphate, tris(2,2,3,3-tetrafluoropropyl) phosphate, tris(1H,1H,5H-octafluoro-n-pentyl) phosphate, bis(2,2,2-trifluoroethyl) phosphite, tris(1,1,1,3,3,3-hexafluoro-2-propyl) phosphate, tris(1,1,1,3,3,3-hexafluoro-2-propyl) phosphite, 1,1-difluoro-2-methylpropyl-2-yl diethyl phosphate, and 2-(2,2,2-trifluoroethoxy)-1,3,2-dioxaphosphacyclopentane 2-oxide; Electrolyte salts The concentration of the fluorinated oxyphosphate compound in the composition is 5 mmol / L to 2000 mmol / L.

2. The composition according to claim 1, characterized in that, The organic cyclic ether reactive diluents include 1,3-dioxolane, 4-methyl-1,3-dioxolane, tert-butyl ethylene oxide-2-carboxylate, methyl (3-(ethylene oxide-2-yl)propyl)carbamate, (2-(ethylene oxide-2-yl)ethyl)carbamate, trimethoxy(8-(ethylene oxide-2-ylmethoxy)octyl)silane, 1,3,5-triglycidyl-S-triazinetrione, and 2-((1-ethoxyethoxy) At least one of the following: (methyl) ethylene oxide, 3-(2,3-epoxypropoxy)propyltrimethoxysilane, 3-(perfluorobutane)-1,2-epoxypropane, 3-(perfluorohexane)-1,2-epoxypropane, 4-[(2,3-epoxypropoxy)methyl]-2,2-dimethyl-1,3-dioxolane, 1,4-bis(epoxyethylene-2-ylmethoxy)butane, and 2,2'-[oxybis(2,1-ethyleneoxymethylene)]bisethylene oxide.

3. The composition according to claim 1, characterized in that, The fluorinated oxyphosphate compounds include tris(2,2,2-trifluoroethyl) phosphates.

4. The composition according to claim 1, characterized in that, The electrolyte salt is selected from one of lithium salt, sodium salt, potassium salt, rubidium salt, calcium salt, magnesium salt, zinc salt, aluminum salt, and tin salt, and the concentration of the electrolyte salt in the composition is 0.1 mol / L to 5 mol / L.

5. The composition according to claim 1, characterized in that, The composition further includes a plasticizer, wherein the plasticizer has a volume fraction of 1% to 70% in the composition.

6. The composition according to claim 5, characterized in that, The plasticizer includes at least one of dimethyl carbonate, diethyl carbonate, ethylene carbonate, methyl propyl carbonate, propylene carbonate, methyl ethyl carbonate, butenyl carbonate, γ-butyrolactone, isopropyl methyl carbonate, tetrahydrofuran, 1,4-butyrolactone, butenyl carbonate, dimethyltetrahydrofuran, 1,2-dimethoxyethane, methyl butyl carbonate, dibutyl carbonate, methyl ester, methyl acetate, dipropyl carbonate, methyl propionate, methyl formate, N-ethylpyrrolidone, N-methyl-2-pyrrolidone, triethyl phosphate, trimethyl phosphate, tripropyl phosphate, dimethyl sulfoxide, succinate, fluoroethylene carbonate, vinylene carbonate, and propylene sulfite.

7. The composition according to claim 1, characterized in that, The composition further includes a film-forming additive, wherein the film-forming additive is present in the composition at a mass percentage of 0.2% to 20%.

8. The composition according to claim 7, characterized in that, The film-forming additive includes at least one of fluoroethylene carbonate, vinylene carbonate, and propylene sulfite.

9. A secondary battery, characterized in that, include: Positive electrode, negative electrode, and A solid polymer electrolyte formed from the composition according to any one of claims 1 to 8.

10. The secondary battery according to claim 9, characterized in that, The secondary battery is any one of lithium metal battery, potassium metal battery, rubidium metal battery, calcium metal battery, magnesium metal battery, zinc metal battery, aluminum metal battery, and tin metal battery.

11. A method for preparing a secondary battery, characterized in that, Includes the following steps: A composition according to any one of claims 1 to 8 is added between the positive electrode and the negative electrode to solidify the composition between the positive electrode and the negative electrode to form a solid polymer electrolyte, thereby obtaining a secondary battery.

12. The preparation method according to claim 11, characterized in that, The curing conditions are specifically: standing at 20℃~80℃ for more than 30 seconds.

13. An electrical appliance, characterized in that, include: The secondary battery according to claim 9 or 10, or the secondary battery prepared by the preparation method according to claim 11 or 12.

Citation Information

Patent Citations

  • Composition for preparing gel electrolyte and electrolyte and battery thereof

    CN115505115A